Manufacturing method of hard carbon-nano silicon sea-island structure spherical negative electrode material
Through the manufacturing method of spherical anode material of hard carbon-nano silicon island structure, the bottleneck of lithium-ion batteries in fast charging and high energy density is solved, low-cost and high-efficiency anode material preparation is achieved, and the performance of 5C fast charging is met. and improves material stability and battery cycle life.
Patent Information
- Application Number
- CN202411426714.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-07
AI Technical Summary
Existing lithium-ion battery negative electrode materials have bottlenecks in fast charging and high energy density. The traditional high-temperature graphitization treatment leads to high costs and large energy consumption, and the material's magnification characteristics and cycle life are insufficient, making it difficult to meet the market's 5C fast charging. demand.
Using the manufacturing method of the spherical anode material of hard carbon-nano silicon island structure, the formation of liquid-solid slurry by melt-kneading of modified asphalt and nanosilicon fine powder is carried out, and thermal isostatic cross-linking and CVD vapor deposition sealing treatment is carried out. , forming a stable hard carbon-nano silicon island structure, achieving high energy density and good magnification characteristics.
It realizes low-cost and high-efficiency lithium-ion battery negative electrode material preparation, has good power characteristics and high energy density, can meet the performance requirements of 5C fast charging, and improves the structural stability of the material and the cycle life of the battery.
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of lithium-ion secondary batteries, and in particular to a high-efficiency, low-cost, high-consistency manufacturing method for negative electrode materials used therein and having the comprehensive characteristics of fast charging and high energy density. Background Art
[0002] As the negative electrode active material of lithium-ion batteries, graphite has high specific capacity, good electrochemical reversibility, relatively low volume expansion rate, high electronic conductivity, and a wide range of raw materials. It is the mainstream negative electrode material for lithium-ion secondary batteries. Commercial graphite negative electrode materials mainly include artificial graphite and asphalt-coated modified natural graphite; currently, the mainstream of the power battery and energy storage battery industry is to use artificial graphite powder as the negative electrode active material, and its market share has exceeded 83%.
[0003] Conventional artificial graphite negative electrode materials use calcined needle coke or asphalt-modified petroleum coke as raw materials, which are crushed / shaped into primary particles / asphalt coating, or modified into secondary particles / carbonized by asphalt bonding, and then enter a high-temperature graphitization furnace for high-temperature graphitization treatment in the high-temperature range of 2900-3200°C, or are crushed / shaped again after cooling after high-temperature graphitization, and then coated with asphalt / carbonized to obtain modified artificial graphite powder; in the development history of lithium battery negative electrode materials, there is also a high-end artificial graphite made by high-temperature graphitization of mesophase carbon microspheres, which is heated in silicone oil to a high-temperature range of about 300-400°C above the softening point of the mesophase asphalt, undergoes high-temperature emulsification to form balls, and after cooling to room temperature, is separated by a centrifuge, washed with benzene or acetone solvents, and dried and then subjected to high-temperature graphitization treatment to obtain spherical artificial graphite negative electrode materials with good power characteristics. Compared with the anisotropic crystal orientation of flaky natural graphite powder, the polycrystalline structure of artificial graphite powder has a better isotropic crystal orientation, a relatively smooth surface, relatively few active sites on the powder surface, a small specific surface area, a higher first efficiency than natural graphite, a relatively long cycle life, and better rate characteristics than natural graphite. The main disadvantage of traditional methods for manufacturing artificial graphite negative electrode materials is that high-temperature graphitization treatment must be carried out, which has a long processing cycle and high energy consumption. During high-temperature graphitization, the burnout of the resistor material filled on the outside of the graphite crucible is large, and the overall cost of artificial graphite negative electrode materials is relatively high.
[0004] Traditional asphalt-coated modified natural graphite uses fine-grained asphalt powder obtained by air flow milling to solid-phase coat natural graphite powder, and then performs carbonization treatment; the advantages of the obtained asphalt-coated modified natural graphite negative electrode material are low cost and high compaction density. The main disadvantage is that the soft carbon coating layer formed after asphalt coating has poor structural stability. During the high-speed stirring process of preparing negative electrode slurry, the soft carbon coating layer is easily damaged when it is impacted during stirring. When the negative electrode plate is subjected to the rolling process, the soft carbon coating layer is also easily crushed and damaged. The specific surface area increases again during actual use. The first efficiency of the whole battery is 3-8% lower than that of artificial graphite, and the battery cycle life is far less than that of artificial graphite. In addition, the flaky polycrystals of natural graphite are anisotropic. When lithium ions are inserted, they are basically embedded from the end face. The effective area for insertion or removal is small, the charge and discharge rate characteristics of the battery are poor, which affects the rate characteristics, and lithium is easily precipitated during fast charging, and the battery safety is poor.
[0005] The uniformity of natural graphite powder coated with asphalt in liquid phase is improved compared with the solid phase coating method. The process of liquid phase coating with asphalt often requires the use of organic solvents such as tetrahydrofuran or aromatic hydrocarbon solvents such as washing oil to dissolve the asphalt into a colloid solution. The natural graphite powder is mixed and coated in the asphalt solution, and vacuum heating is required to remove the solvent. There are flammable and explosive hazards and environmental load pressure. The soft carbon coating layer formed after carbonization also has the problem of structural instability, and the battery performance is not enough to compete with batteries made of artificial graphite.
[0006] With the market demand for electric vehicles to solve mileage anxiety and reduce costs, the fast charging performance requirements for negative electrode active materials have increased from 1.3C in the early market to 4C or even 5C fast charging. Traditional asphalt-coated natural graphite or artificial graphite negative electrode materials have encountered rate performance bottlenecks, and are prone to lithium deposition during fast charging, making it difficult to meet the market demand for 5C fast charging performance.
[0007] Hard carbon negative electrode materials have superior lithium ion transmission performance and excellent rate characteristics. Their disadvantage is their nano-scale microporous structure. When used as negative electrode materials for lithium-ion batteries, hard carbon powders have the disadvantages of low true density, low compaction density, and low initial efficiency. The true density of conventional hard carbon powder materials is generally between 1.55-1.65 g / cm3. When conventional hard carbon powder materials are used as negative electrode materials for lithium batteries, while improving the battery rate characteristics, they seriously reduce the compaction density of the electrode and the energy density of the battery. The energy density of conventional hard carbon negative electrode materials is low and it is difficult to meet the high energy density requirements of power batteries. When traditional hard carbon powder materials are used in lithium-ion batteries, the BET specific surface area is large and the battery initial efficiency is low.
[0008] In order to improve the energy density of the battery while meeting the fast charging characteristics, document CN117012936A proposes to use modified asphalt to granulate graphite particles to obtain secondary particles of a hard carbon-soft carbon composite structure. In order to improve the bonding strength of the interface between the two, it is proposed to use sodium hydroxide, potassium hydroxide, sodium carbonate or sodium bicarbonate and other pore-forming agents to blend with graphite particles and then calcine them, and perform high-temperature reaction dissolution to form pores on the surface of the graphite powder.
[0009] Document CN115312731A proposes to perform acid activation on graphite powder and introduce an oxidizing atmosphere at 200 to 500°C to perform surface oxidation etching to form pores. The oxidants of the modified asphalt include hydrogen peroxide, peracetic acid, sodium dichromate, chromic acid, potassium dichromate, etc. The modified asphalt is coated and carbonized to form a hard carbon-graphite composite negative electrode active material. This method performs acid washing and activation on the surface of the graphite core, which has an environmental load problem; this method is prone to generate bubbles during the oxidation and cross-linking treatment of asphalt.
[0010] Document CN109037603A proposes a novel method for preparing asphalt-based spherical porous doped modified hard carbon negative electrode materials. After high-temperature coal-based asphalt is crushed, a terephthalaldehyde crosslinking agent is added under nitrogen protection to carry out a crosslinking reaction, followed by the addition of ammonium persulfate oxidant and the introduction of oxygen for oxidation treatment to obtain high-temperature crosslinked oxidized asphalt; then spray granulation is performed to form balls; carbonization treatment and high-temperature graphitization are performed; the document points out that the modified spherical hard carbon negative electrode material obtained by this method has good rate characteristics, a 30C / 1C capacity retention rate of greater than 98%, a reversible specific capacity of greater than 400mAh / g, an initial efficiency of greater than 80%, and a capacity retention rate of greater than 85% after 500 cycles. According to the data in the document, the true density of the hard carbon negative electrode material prepared by asphalt crosslinking modification is 1.62g / cm 3 , compacted density 1.25g / cm 3 It is too low and cannot take into account the high energy density requirements of lithium-ion batteries. Although a certain degree of powder sphericity can be obtained by conventional spray granulation and balling technology, many tiny bubbles are easily generated during high-temperature cross-linking of the modified asphalt precursor, which affects the compressive strength and specific surface area of the powder material. In the manufacturing process of the negative electrode sheet, the negative electrode active material powder with bubbles is easily crushed during the rolling process, and the specific surface area of the powder increases rapidly, the initial efficiency of the battery is seriously reduced, and the battery cycle life will also be negatively affected.
[0011] At present, the technology of using CVD vapor deposition of nano-silicon on porous carbon matrix to manufacture silicon-carbon negative electrode materials is in the ascendant. High-purity silane gas is used as the silicon source, and porous carbon powder is chemically vapor deposited in a fluidized state at 450°C. This process has small single-furnace production capacity, high energy consumption, high fixed asset investment, and high product manufacturing cost.
[0012] In order to overcome the above-mentioned shortcomings and deficiencies of the prior art, the present invention is particularly proposed to provide a lithium-ion battery negative electrode material with good rate characteristics, high energy density characteristics, low manufacturing cost, stable product structure, good adaptability to the process requirements of lithium battery manufacturing, and stable performance. Summary of the invention
[0013] The present invention proposes a method for manufacturing a hard carbon-nano silicon sea island structure spherical negative electrode material, characterized in that the hard carbon component serves as the ocean in the sea island structure and serves as a complete and interconnected carrier; the nano silicon powder serves as the small islands in the sea island structure and is dispersed in the ocean matrix of the hard carbon component; the precursor of the hard carbon component is prepared by melting and kneading modified asphalt (MP) into a melt, and then the melt is mixed evenly with the nano silicon powder to prepare a thermoplastic liquid-solid slurry, which is then dispersed into balls by water-based homogeneous emulsification, hot isostatic pressing cross-linking and curing treatment, and subsequent primary carbonization treatment and CVD vapor deposition sealing treatment; (MP) has the following technical characteristics: it can achieve controllable chemical cross-linking, has a thermoplastic processing window, and can be used in a wider range of processes. Chemical cross-linking and curing are achieved under high temperature and isostatic pressure to obtain a semi-finished spherical particle that is not easy to stick together; (MP) a low-viscosity liquid melt is formed after initial melting, and during the hot processing of kneading and mixing with nano-silicon powder, even if a part of the chemical cross-linking reaction occurs in the melt, it still has thermoplasticity, which can ensure that the mixing and dispersion into a uniform liquid-solid slurry, and the liquid-solid slurry is dispersed into micron-sized spherical particles (hereinafter referred to as PCSP) by a homogenous emulsification method using hot water, and the PCSP is evenly distributed in the water-based emulsion; the homogenized and emulsified water-based emulsion is placed in a high-pressure container, and the PCSP therein is subjected to a hot isostatic cross-linking and curing treatment in a high-temperature and high-pressure environment, and the hot isostatic cross-linking and curing treatment is carried out at a temperature between 135°C The material temperature is lowered to 190°C, and compressed air, high-pressure oxygen, high-pressure nitrogen, compressed air mixed with ozone, or one or a combination of these gases is pumped into the high-pressure container to control the ambient pressure (P1) inside the high-pressure container to be at least 0.20MPa to 1.60MPa higher than the saturated vapor pressure (P0) of hot water corresponding to the material temperature. The superheated water at high temperature and high pressure in the water-based emulsion is used as a medium for transmitting static pressure, and the cross-linking and curing time is controlled to be between 10 minutes and 3 hours. After the treatment, the PCSP in the water-based emulsion is cross-linked and cured more fully, and bubbles are prevented from being generated in the PCSP. Spray drying is continued or the material is slowly cooled and depressurized in steps and then dried in a normal pressure oven to obtain a cross-linked and cured product. Spherical particle powder (hereinafter referred to as WCSP); the WCSP is further subjected to a carbonization treatment and a subsequent CVD surface sealing treatment in a loose or vibrated physical state, wherein the modified asphalt component of the WCSP after cross-linking and curing is converted into a marine component mainly composed of a hard carbon structure, and the nano-silicon powder is dispersed in the marine matrix of the hard carbon component in an island shape, and after cooling to below 200°C and being taken out of the furnace, it is passed through a 200-mesh vibrating screen or air flow classification to remove magnetic foreign matter, and a hard carbon-nano-silicon sea island structure spherical negative electrode material with both power characteristics and high energy density characteristics is obtained, wherein the average particle size D50 is between 2 and 12 microns, and D90 is less than 16 microns; the reversible specific capacity is between 500 and 2060 mAh / g, and the BET specific surface area is less than or equal to 6m 2 / g, the first coulombic efficiency is greater than or equal to 85%, and the 5C / 1C charging capacity ratio is greater than 88%.
[0014] The method for manufacturing the hard carbon-nano silicon island structure spherical negative electrode material of the present invention comprises the following process steps:
[0015] Step 1 Preparation of nano silicon powder
[0016] The particle size D90 of the raw material of nano silicon powder is controlled to be less than 150 nanometers, and it is produced by vapor deposition condensation method; or the hypereutectic Al-Si alloy is used to control the primary precipitation size of silicon element in the strip by water-cooled copper roller rapid cooling and strip fast solidification method, and then artificial aging at 70℃-130℃ for 12 hours to 96 hours is used to control the precipitation and growth size of nano silicon, and then hydrochloric acid or dilute nitric acid is used for pickling and dissolving to remove aluminum elements in the alloy, and then centrifugal separation, pure water washing, flotation, drying, to obtain nano silicon powder with a particle size D90 less than 150 nanometers;
[0017] Step 2 Preparation of thermoplastic liquid-solid slurry
[0018] The thermoplastic liquid-solid slurry is composed of a partially cross-linked modified asphalt (MP) melt as a liquid phase component, and the cross-linking and curing process is delayed to after homogenization and emulsification into balls by controlling the thermal cracking kinetics of the peroxide cross-linking agent in the (MP). The above-mentioned nano-silicon powder is used as a solid phase component;
[0019] The modified asphalt (MP) uses the following raw materials:
[0020] Main raw material A: medium-temperature asphalt with a softening point between 70°C and 95°C and a coking value greater than 35%; the weight proportion of main raw material A in the (MP) raw materials is greater than or equal to 40wt.%;
[0021] Auxiliary raw material B: As a melt strength regulator, a high-temperature asphalt with a relatively high molecular weight, a softening point between 96°C and 180°C, and a coking value greater than 45% is used; the weight proportion of auxiliary raw material B in the (MP) raw material is between 0-30wt.%;
[0022] Auxiliary raw material C: as a viscosity modifier and participating in chemical crosslinking, one of naphthenic oil with an open flash point greater than 215°C, coal tar, ethylene tar, vacuum residue, naphthalene asphalt, ethylene-vinyl acetate (EVA) copolymer with a melting point between 55-90°C, styrene-butadiene rubber (SBR) or a combination thereof is used; the weight proportion of auxiliary raw material C in the (MP) raw material is between 10-35wt.%;
[0023] Auxiliary raw material D: using peroxide crosslinking agent, having controllable thermal decomposition kinetics, 1 minute half-life temperature greater than 165 ° C, 1 hour half-life temperature greater than 130 ° C, 10 hours half-life temperature between 110-125 ° C; including diisopropylbenzene peroxide (DCP for short), di-tert-butyl diisopropylbenzene peroxide (BIPB for short), 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane (BIPB for short) or a combination thereof; the weight proportion of auxiliary raw material D in the (MP) raw material is between 1.0-4.0wt.%;
[0024] Auxiliary raw material E: a small molecule auxiliary cross-linking agent with olefin multifunctional groups and having grafting and bridging functions, including triallyl isocyanurate (TAIC for short), triallyl cyanurate (TAC for short), vinyl triethoxysilane (A1522 for short), etc.; the weight proportion of auxiliary raw material E in the (MP) raw material is between 0-8.0wt.%;
[0025] The A / B / C in the above raw materials are first heated in a kneader at a temperature range of 115°C-190°C, and kneaded and mixed uniformly; then nano silicon powder at room temperature or preheated to 110°C-190°C is added, and the kneading and mixing is continued for 30min-120min; then the material temperature is controllably cooled to 110°C-130°C; then a peroxide crosslinking agent and an auxiliary crosslinking agent are added, and the kneading is continued for 20min-240min, and the free radicals generated by thermal decomposition of the peroxide crosslinking agent and the above raw materials are heated, kneaded and mixed together, and a CC crosslinking bond structure is generated through a free radical addition reaction or a double bond addition reaction, or a high-activity oxide formed after the decomposition of the peroxide reacts with the above hydrocarbon polymer raw materials through hydrogen abstraction to generate free radicals, so as to achieve a partial chemical crosslinking reaction between the polymers inside the (MP), while the liquid-solid slurry still maintains a thermoplastic physical state;
[0026] The order of adding materials can also be adjusted to prepare a thermoplastic liquid-solid slurry by adopting the following kneading and mixing process: the above raw materials A / B / C are first heated in a kneader at a temperature range of 110°C-190°C, and kneaded and mixed evenly; the material temperature is controllably cooled to 110°C-130°C; then a peroxide crosslinking agent and an auxiliary crosslinking agent are added, and the kneading and mixing are continued for 10min-60min; finally, nano-silicon powder at room temperature or preheated to 110°C-130°C is added, and the kneading and mixing are continued for 30min-240min; a partial chemical crosslinking reaction is achieved between the polymers inside the liquid-solid slurry, while the liquid-solid slurry still maintains a thermoplastic physical state;
[0027] Then the liquid-solid slurry is controllably cooled to control the material temperature between 90-100°C, and the liquid-solid slurry material still maintains a thermoplastic physical state;
[0028] Step 3: Homogenize and emulsify the liquid-solid slurry in hot water and disperse it into balls
[0029] Hot water is used as a medium, the temperature of the hot water is controlled at 90-100° C., 0.5-4wt.% of a nonionic surfactant and 0.2-2.5wt.% of a water-soluble polymer dispersant are pre-added in the hot water and dissolved evenly; the above-mentioned liquid-solid slurry material that is still thermoplastic after being cooled to a temperature range of 90-100° C. is homogenized and emulsified; the nonionic surfactant includes one of polyoxyethylene-polyoxypropylene copolymer, fatty alcohol polyoxyethylene ether, and polyvinyl pyrrolidone or a combination thereof; the dispersant includes one of polyvinyl alcohol (PVA), hydroxypropyl methylcellulose (HEMC), hydroxyethyl cellulose (HEC), sodium carboxymethyl cellulose (CMC), polyoxyethylene (PEO) and other water-soluble polymers or a combination thereof; the above-mentioned thermoplastic liquid-solid slurry is homogenized and emulsified in hot water by utilizing the high-speed shear dispersion function of the homogenization emulsification equipment and the comprehensive effect of the liquid-solid surface tension in the water-based emulsion to disperse and form micron-sized spherical particles (Partly Cross-linking Spherical Semi-finished Products) Paticles, hereinafter referred to as PCSP), PCSP is evenly distributed in the water-based emulsion, and the solid content is controlled between 15wt.% and 45wt.%; too high a solid content in the emulsion is likely to cause demulsification and fusion, and too low a solid content has too low a production efficiency;
[0030] Step 4 Hot isostatic pressing cross-linking curing treatment
[0031] The homogenized and emulsified water-based emulsion is placed in a high-pressure container, and the PCSP therein is subjected to hot isostatic pressing cross-linking curing treatment in a high-temperature and high-pressure environment. During the treatment, the material temperature is between 135°C and 190°C. Compressed air, high-pressure oxygen, high-pressure nitrogen, compressed air mixed with ozone, or a combination of gases thereof are pumped into the high-pressure container to adjust the environmental pressure (P1) inside the high-pressure container to be at least 0.20MPa to 1.20MPa higher than the saturated vapor pressure (P0) of hot water corresponding to the material temperature. The superheated water at high temperature and high pressure in the water-based emulsion is used as a medium for transmitting static pressure. The cross-linking curing time is controlled to be between 30 minutes and 3 hours. After the hot isostatic pressing treatment, the PCSP in the water-based emulsion is cross-linked and cured, and bubbles are prevented from being generated in the PCSP. Spray drying is continued or the material is slowly cooled and depressurized in a stepwise manner and then dried in a normal pressure oven to obtain cross-linked and cured spherical granular powder (Wholly Cross-linked Spherical Particles, hereinafter referred to as WCSP); the dried WCSP is further subjected to a carbonization treatment and a subsequent CVD surface sealing treatment in a loose or vibrated physical state;
[0032] Step 5: Carbonization treatment
[0033] The spherical particle powder WCSP which is not easy to stick after being fully cross-linked and cured is passed through a 200-mesh vibrating screen or subjected to air flow particle size sorting, and then subjected to a carbonization treatment in a loose or compacted natural stacking physical state: first, the material is heated to 190°C-230°C under the protection of air or oxidizing atmosphere or inert atmosphere, and a pulse high-pressure oxidation treatment is carried out in this temperature range for 0-12 hours. The container is filled with high-pressure oxygen or compressed air or compressed air mixed with ozone at a pressure between 0.40-1.6MPa. In each cycle, the high pressure is maintained. The peak time of the pressure pulse is between 30min-2h, and then a part of the internal gas is discharged to reduce the pressure to 0.20-0.80MPa, and this cycle is repeated ON times; then the material is heated step by step to a maximum carbonization temperature between 700-1200°C under vacuum or inert atmosphere protection with positive pressure, and maintained for 1-6 hours. After the material is cooled, a spherical powder semi-finished product with a hard carbon-nano silicon island structure with nano-scale openings on the surface is obtained. At this time, the BET specific surface area of the spherical powder semi-finished product is greater than 18 square meters / gram, and a subsequent CVD surface sealing treatment is performed;
[0034] Step 6: Use CVD to achieve surface sealing
[0035] After the carbonization treatment in the above steps, a carbon source-containing gas such as methane, propane or ethylene is introduced into the material in a fluidized state, and conventional CVD chemical vapor deposition is used to achieve surface sealing; or pulse high-pressure chemical vapor deposition (PH-CVD) is used to achieve surface sealing when the material is in a loose or vibrated state: an inert gas with a pressure between 0.60 and 1.60 MPa is used as a carrier gas, and cyclohexane liquid or other hydrocarbons are used as a carbon source. The nanoscale micropores distributed on the surface of the spherical powder semi-finished product formed after the above-mentioned carbonization are used to adsorb the active gas polymer clusters formed after thermal evaporation or thermal cracking of the carbon source. After subsequent high-temperature thermal cracking, thermal polycondensation and other complex physical and chemical changes, an amorphous carbon coating layer is formed on the surface of the powder or inside the open micropores, thereby achieving surface sealing, reducing the BET specific surface area, and improving the battery's initial efficiency. The technical purpose; pulse high-pressure chemical vapor deposition (PH-C The specific technical operation of VD is as follows: when the material heating temperature is between 200℃-600℃, pulse high pressure chemical vapor deposition adopts the following multiple variable pressure cycle operations: use the internal gas pressure in the pressure range of 0.60-1.60MPa for high pressure pulse heat treatment for 1-2 hours, and then reduce the pressure to the low pressure range of 0.20-0.80MPa, and perform such pulse variable pressure for 6-20 cycles to achieve mass transfer and adsorption of active gas polymer clusters between powder gaps and on the surface of powder; after subsequent heating to the temperature range of 600℃-1300℃ for secondary carbonization treatment, pyrolytic carbon-type amorphous carbon is formed on the surface of the powder to achieve surface sealing and reduce the BET specific surface area of the spherical powder. After cooling to below 200℃ and taking out of the furnace, it is passed through a 200-mesh vibrating screen or air flow classification to remove magnetic foreign matter to obtain a hard carbon-graphite sea island structure spherical negative electrode material finished product, and its BET specific surface area is less than or equal to 6m 2 / g.
[0036] Taking into account the volume expansion effect of nanosilicon during charging when the hard carbon-nanosilicon sea island structure spherical negative electrode material is applied to lithium ion batteries, in order to take into account both the energy density and cycle life of the battery, the present invention more preferably controls the weight ratio of nanosilicon powder and precursor of the hard carbon component in the raw material to be between 1:10 and 1:20, and utilizes the pore volume of the nanoscale micropores present in the hard carbon component to provide compensation space for the expansion of nanosilicon during charging. The obtained hard carbon-nanosilicon sea island structure spherical negative electrode material has a gram capacity of between 500 and 750 mAh / g, and the lithium ion battery made therefrom has a 3C charge / 3C discharge cycle life of more than 1000 times.
[0037] The method of the present invention has the following positive technical effects: in a thermoplastic physical state, a liquid-solid slurry with a certain viscosity composed of a partially chemically cross-linked modified asphalt hard carbon precursor and nano-silicon powder is homogenized and emulsified and dispersed into balls in hot water, which has the advantages of low production energy consumption, high production efficiency and high material yield; the emulsion after dispersion into balls is cross-linked and cured by hot isostatic pressing to obtain a spherical powder after chemical cross-linking and curing, avoiding the defect of cross-linking reaction of semi-finished products under normal pressure and easy generation of bubbles in the powder, thereby ensuring the structural stability and performance stability of the composite powder; avoiding the defect of powder structure damage caused by severe adhesion between powders after carbonization treatment and the need for crushing in conventional asphalt coating processes; the method of the present invention lays a foundation for material processing for improving the structural stability of composite powder negative electrode materials and the initial efficiency and cycle life of batteries; the hard carbon-nano-silicon island structure spherical negative electrode material of the present invention has good power characteristics and high energy density when applied to lithium-ion batteries.
[0038] In order to better illustrate the technical purpose, technical solution and beneficial effects of the present invention, further explanation is given below in conjunction with specific embodiments.
[0039] Example 1: A hard carbon-graphite sea island structure spherical negative electrode material is prepared by the following manufacturing method:
[0040] Step 1 Preparation of nano silicon powder
[0041] 1250 parts by weight of nano silicon powder, using hypereutectic aluminum silicon alloy A187-13Si, firstly obtain a strip with a thickness of 0.03 mm by a water-cooled copper roller rapid cooling and strip spinning rapid solidification process, then artificially ageing at 95°C for 60 hours to control the precipitation and growth size of nano silicon, then pickling with hydrochloric acid or dilute nitric acid to dissolve and remove aluminum elements, then washing with pure water, flotation, and drying to obtain nano silicon powder with a particle size D90 between 80 and 110 nanometers;
[0042] Step 2 Preparation of thermoplastic liquid-solid slurry
[0043] Modified asphalt (MP) totals 19,000 parts by weight, using the following raw materials:
[0044] Main raw material A: medium-temperature asphalt with a softening point between 80°C and 90°C and a coking value greater than 45%; the weight proportion of main raw material A in the (MP) raw materials is 60.5wt.%;
[0045] Auxiliary raw material B: high-temperature asphalt with a softening point between 110°C and 115°C and a coking value greater than 52%; the weight proportion in the (MP) raw material is 11wt.%;
[0046] Auxiliary raw material C: using styrene-butadiene rubber of grade YH-792E, the structural ratio of styrene-butadiene is 40:60, and the weight proportion in the (MP) raw material is 24wt.%;
[0047] Auxiliary raw material D: The peroxide crosslinking agent is di-tert-butyl diisopropylbenzene peroxide (referred to as BIPB); the weight proportion in the (MP) raw material is 3wt.%;
[0048] Auxiliary raw material E: triallyl isocyanurate (TAIC for short); its weight proportion in the (MP) raw material is 1.5wt.%;
[0049] The raw materials A / B / C are first heated in a vacuum kneader at a temperature range of 125-135°C, and kneaded and mixed uniformly; the material temperature is controllably cooled to 115-125°C, and then a peroxide crosslinking agent and an auxiliary crosslinking agent are added, and the kneading and mixing are continued for 15 minutes; then nano silicon powder preheated to 120°C is added, and the kneading and mixing are continued for 30 minutes; the liquid-solid slurry is controllably cooled, and the material temperature is controlled to be between 96-99°C, and the liquid-solid slurry material still maintains a thermoplastic physical state;
[0050] Step 3: Homogenize and emulsify the liquid-solid slurry in hot water and disperse it into balls
[0051] Hot water is used as a medium, and the temperature of the hot water is controlled between 96-99°C. 2wt.% of non-ionic surfactant is pre-added in the hot water, and a polyoxyethylene-polyoxypropylene copolymer with a brand number of L44 produced by Jiangsu Haian Petrochemical is used; the amount of dispersant added is 0.5wt.%, and the brand of polyvinyl alcohol 17-88 produced by Beijing Organic Chemical Plant is used, and it is evenly dissolved; the above-mentioned liquid-solid slurry material that is still thermoplastic after being cooled to a temperature range of 96-99°C is homogenized and emulsified; using a self-made special equipment for homogenizing emulsified asphalt, the above-mentioned thermoplastic liquid-solid slurry is homogenized in hot water, dispersed evenly, and prepared into a spherical fine granular semi-finished product evenly distributed in the hot water in an emulsion state;
[0052] Step 4 Hot isostatic pressing cross-linking curing treatment
[0053] The homogenized and emulsified water-based emulsion is placed together in a high-pressure container, and the PCSP therein is subjected to hot isostatic pressing cross-linking treatment. The material temperature is between 155°C and 160°C during the hot isostatic pressing cross-linking treatment, and high-temperature and high-pressure superheated water is used as a medium for transmitting pressure. By pumping compressed air into the high-pressure container, the environmental pressure (P1) inside the high-pressure container is controlled to be between 1.00-1.20MPa, and the cross-linking time is controlled to be between 90 minutes and 120 minutes. After the PCSP in the water-based emulsion is cross-linked and cured, the temperature and pressure are reduced in steps, and the PCSP is dried in a normal pressure oven at 110°C to obtain a cross-linked and cured spherical particle powder WCSP, and the WCSP is further subjected to a carbonization treatment and a subsequent pulse high-pressure CVD surface sealing treatment in a loose physical state;
[0054] Step 5: Carbonization treatment
[0055] The above-mentioned non-sticky spherical powder semi-finished product is passed through a 200-mesh vibrating screen, loosely packed and placed in a tooling. After entering the furnace, the material is first heated to 190°C-200°C in a high-pressure oxidizing atmosphere, and a pulse high-pressure oxidation treatment is performed in this temperature range for 5 hours. The container is filled with compressed air mixed with ozone at a pressure of 0.60MPa. In each cycle, the peak time of the high-pressure pulse is maintained for 55 minutes, and then a part of the internal gas is discharged to reduce the pressure inside the container to 0.30MPa. This cycle is repeated 8 times; then a carbonization treatment is continued under the protection of a nitrogen atmosphere, and the material is heated to 350°C at a heating rate of 1°C / min and kept warm for 3 hours; heated to 460°C at a heating rate of 1°C / min and kept warm for 3 hours; heated to 600°C at a heating rate of 2°C / min and kept warm for 2 hours; heated to 900°C at a heating rate of 5°C / min and kept warm for 2 hours; wait for the material to cool to 200°C for subsequent CVD sealing treatment;
[0056] Step 6: Use polymer cluster pulse high pressure chemical vapor deposition to achieve surface sealing
[0057] Using nitrogen as carrier gas and naphthenic oil liquid K4010 as carbon source, the material heating temperature is between 200-600℃, and the pulse high pressure chemical vapor deposition adopts the following multiple variable pressure cycles: high pressure pulse heat treatment is carried out for 2 hours at a pressure between 0.60-0.70MPa, and then the pressure is reduced to a low pressure range between 0.30-0.40MPa. The pulse variable pressure is cycled 12 times to achieve mass transfer and adsorption of active gas polymer clusters between powder gaps and on the surface of powder; followed by The secondary carbonization treatment was carried out at a heating rate of 3°C / min from 600°C to 1200°C for 3 hours to form amorphous carbon materials of pyrolytic carbon on the surface of the powder, achieving the technical purpose of reducing the BET specific surface area by sealing treatment, and further optimizing the microstructure of hard carbon; after cooling to below 200°C and taking out of the furnace, air flow classification was used to remove magnetic foreign matter to obtain a spherical hard carbon-graphite sea island structure composite negative electrode material product, with an average particle size D50 between 8 and 10 microns and D90 less than 15 microns; the true density was 1.66 g / cm 3 , reversible specific capacity is 600mAh / g, BET specific surface area is 3.75m 2 / g, the first coulombic efficiency is greater than 89%, the 5C / 1C charging capacity ratio is greater than 92%, and the cylindrical 18650 battery made with lithium iron phosphate positive electrode has a 3C / 3C charge and discharge cycle life of more than 1600 times.
Claims
1. A method for manufacturing a hard carbon-nano silicon island structure spherical negative electrode material, characterized in that: The hard carbon component acts as the ocean in the island structure and as a complete interconnected carrier; the nano-silicon powder acts as the small islands in the island structure and is dispersed in the ocean matrix of the hard carbon component; the precursor of the hard carbon component is modified asphalt (MP) and is melt-mixed into a melt, and then mixed evenly with the nano-silicon powder to prepare a thermoplastic liquid-solid slurry, which is then dispersed into balls by water-based homogeneous emulsification, hot isostatic pressing cross-linking and curing treatment, and subsequent primary carbonization treatment and CVD vapor deposition sealing treatment; (MP) has the following technical characteristics: it can achieve controllable chemical cross-linking, has a thermoplastic processing window, and can achieve chemical cross-linking and curing at higher temperatures and isostatic pressures to obtain spherical particles that are not easy to stick together. The semi-finished product (MP) is a low-viscosity liquid melt formed after initial melting. During the hot processing of kneading and mixing with nano-silicon powder, even if a part of the chemical cross-linking reaction occurs in the melt, it still has thermoplasticity, which can ensure that the mixing and dispersion into a uniform liquid-solid slurry is achieved. The liquid-solid slurry is dispersed into micron-sized spherical particles (hereinafter referred to as PCSP) by a homogenizing emulsification method using hot water. The PCSP is evenly distributed in the water-based emulsion; the homogenized and emulsified water-based emulsion is placed inside a high-pressure container, and the PCSP therein is subjected to a hot isostatic pressing cross-linking and curing treatment in a high-temperature and high-pressure environment. The hot isostatic pressing cross-linking and curing treatment uses a material temperature between 135°C and 190°C, and the high-pressure container is filled with the emulsified water-based emulsion. Compressed air, high-pressure oxygen, high-pressure nitrogen, compressed air mixed with ozone, one of the gases or a combination of gases are pumped into the high-pressure container to control the ambient pressure (P1) inside the high-pressure container to be at least 0.20 MPa to 1.60 MPa higher than the saturated vapor pressure (P0) of hot water corresponding to the temperature of the material, and the superheated water at high temperature and high pressure in the water-based emulsion is used as a medium for transmitting static pressure. The cross-linking and curing time is controlled to be between 10 minutes and 3 hours. After the treatment, the PCSP in the water-based emulsion is relatively fully cross-linked and cured, and bubbles are prevented from being generated in the PCSP; spray drying is continued or the material is slowly cooled and depressurized in steps and then dried in a normal pressure oven to obtain cross-linked and cured spherical particle powder (hereinafter referred to as WCSP); the WCSP is subjected to a carbonization treatment and a subsequent CVD surface sealing treatment in a loose or vibrated physical state, wherein the modified asphalt component of the WCSP after cross-linking and curing is converted into a marine component mainly composed of a hard carbon structure, and the nano-silicon powder is dispersed in the marine matrix of the hard carbon component in an island shape, and after cooling to below 200°C and being taken out of the furnace, it is passed through a 200-mesh vibrating screen or air flow classification to remove magnetic foreign matter, thereby obtaining a hard carbon-nano-silicon sea island structure spherical negative electrode material product with both power characteristics and high energy density characteristics, wherein the average particle size D50 is between 2 and 12 microns, and the D90 is less than 16 microns; the reversible specific capacity is between 500mAh / g and 2060mAh / g, and the BET specific surface area is less than or equal to 6m 2 / g, the first coulombic efficiency is greater than or equal to 85%, and the 5C / 1C charging capacity ratio is greater than 88%.
2. The method for manufacturing the hard carbon-nano silicon island structure spherical negative electrode material according to claim 1, characterized in that: The process steps include: Step 1 Preparation of nano silicon powder The particle size D90 of the raw material of nano silicon powder is controlled to be less than 150 nanometers, and it is produced by vapor deposition condensation method; or the primary precipitation size of silicon element is controlled by using hypereutectic Al-Si alloy through water-cooled copper roller rapid cooling and strip spinning rapid solidification method, and then artificial aging at 70℃-130℃ for 12 hours to 96 hours is used to control the precipitation and growth size of nano silicon, and then hydrochloric acid or dilute nitric acid is used for pickling and dissolving to remove aluminum elements in the alloy, and then centrifugal separation, pure water washing, flotation, drying, to obtain nano silicon powder with a particle size D90 less than 150 nanometers; Step 2 Preparation of thermoplastic liquid-solid slurry The thermoplastic liquid-solid slurry is composed of a partially cross-linked modified asphalt (MP) melt as a liquid phase component, and the cross-linking and curing process is delayed to after homogenization and emulsification into balls by controlling the thermal cracking kinetics of the peroxide cross-linking agent in the (MP). The above-mentioned nano-silicon powder is used as a solid phase component; The modified asphalt (MP) uses the following raw materials: Main raw material A: medium-temperature asphalt with a softening point between 70°C and 95°C and a coking value greater than 35%; the weight proportion of main raw material A in the (MP) raw materials is greater than or equal to 40wt.%; Auxiliary raw material B: As a melt strength regulator, a high-temperature asphalt with a relatively high molecular weight, a softening point between 96°C and 180°C, and a coking value greater than 45% is used; the weight proportion of auxiliary raw material B in the (MP) raw material is between 0-30wt.%; Auxiliary raw material C: as a viscosity modifier and participating in chemical crosslinking, one of naphthenic oil with an open flash point greater than 215°C, coal tar, ethylene tar, vacuum residue, naphthalene asphalt, ethylene-vinyl acetate (EVA) copolymer with a melting point between 55-90°C, styrene-butadiene rubber (SBR) or a combination thereof is used; the weight proportion of auxiliary raw material C in the (MP) raw material is between 10-35wt.%; Auxiliary raw material D: using peroxide crosslinking agent, having controllable thermal decomposition kinetics, 1 minute half-life temperature greater than 165 ° C, 1 hour half-life temperature greater than 130 ° C, 10 hours half-life temperature between 110-125 ° C; including diisopropylbenzene peroxide (DCP for short), di-tert-butyl diisopropylbenzene peroxide (BIPB for short), 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane (BIPB for short) or a combination thereof; the weight proportion of auxiliary raw material D in the (MP) raw material is between 1.0-4.0wt.%; Auxiliary raw material E: a small molecule auxiliary cross-linking agent with olefin multifunctional groups and having grafting and bridging functions, including triallyl isocyanurate (TAIC for short), triallyl cyanurate (TAC for short), vinyl triethoxysilane (A1522 for short), etc.; the weight proportion of auxiliary raw material E in the (MP) raw material is between 0-8.0wt.%; The A / B / C in the above raw materials are first heated in a kneader at a temperature range of 115°C-190°C, and kneaded and mixed uniformly; then nano silicon powder at room temperature or preheated to 110°C-190°C is added, and the kneading and mixing is continued for 30min-120min; then the material temperature is controllably cooled to 110°C-130°C; then a peroxide crosslinking agent and an auxiliary crosslinking agent are added, and the kneading is continued for 20min-240min, and the free radicals generated by thermal decomposition of the peroxide crosslinking agent and the above raw materials are heated, kneaded and mixed together, and a CC crosslinking bond structure is generated through a free radical addition reaction or a double bond addition reaction, or a high-activity oxide formed after the decomposition of the peroxide reacts with the above hydrocarbon polymer raw materials through hydrogen abstraction to generate free radicals, so as to achieve a partial chemical crosslinking reaction between the polymers inside the (MP), while the liquid-solid slurry still maintains a thermoplastic physical state; The order of adding materials can also be adjusted to prepare a thermoplastic liquid-solid slurry by adopting the following kneading and mixing process: the above raw materials A / B / C are first heated in a kneader at a temperature range of 110°C-190°C, and kneaded and mixed evenly; the material temperature is controllably cooled to 110°C-130°C; then a peroxide crosslinking agent and an auxiliary crosslinking agent are added, and the kneading and mixing are continued for 10min-60min; finally, nano-silicon powder at room temperature or preheated to 110°C-130°C is added, and the kneading and mixing are continued for 30min-240min; a partial chemical crosslinking reaction is achieved between the polymers inside the liquid-solid slurry, while the liquid-solid slurry still maintains a thermoplastic physical state; Then the liquid-solid slurry is controllably cooled to control the material temperature between 90-100°C, and the liquid-solid slurry material still maintains a thermoplastic physical state; Step 3: Homogenize and emulsify the liquid-solid slurry in hot water and disperse it into balls Hot water is used as a medium, and the temperature of the hot water is controlled between 90-100° C. 0.5-4wt.% of a nonionic surfactant and 0.2-2.5wt.% of a water-soluble polymer dispersant are pre-added in the hot water and dissolved evenly; the above-mentioned liquid-solid slurry material that is still thermoplastic after being cooled to a temperature range of 90-100° C. is homogenized and emulsified; the nonionic surfactant includes one of polyoxyethylene-polyoxypropylene copolymer, fatty alcohol polyoxyethylene ether, and polyvinyl pyrrolidone or a combination thereof; the dispersant includes one of polyvinyl alcohol (PVA), hydroxypropyl methylcellulose (HEMC), hydroxyethyl cellulose (HEC), sodium carboxymethyl cellulose (CMC), polyoxyethylene (PEO) and other water-soluble polymers or a combination thereof; the above-mentioned thermoplastic liquid-solid slurry is homogenized and emulsified in hot water by utilizing the high-speed shear dispersion function of the homogenization emulsification equipment and the combined effect of the liquid-solid surface tension in the water-based emulsion to disperse and form micron-sized spherical particles (Partly Cross-linking Spherical Semi-finished Products) Paticles, hereinafter referred to as PCSP), PCSP is evenly distributed in the water-based emulsion, and the solid content is controlled between 15wt.% and 45wt.%; Step 4 Hot isostatic pressing cross-linking curing treatment The homogenized and emulsified water-based emulsion is placed in a high-pressure container, and the PCSP therein is subjected to hot isostatic pressing cross-linking curing treatment in a high-temperature and high-pressure environment. During the treatment, the material temperature is between 135°C and 190°C. Compressed air, high-pressure oxygen, high-pressure nitrogen, compressed air mixed with ozone, or one or a combination of gases thereof are pumped into the high-pressure container to adjust the environmental pressure (P1) inside the high-pressure container to be at least 0.20MPa to 1.60MPa higher than the saturated vapor pressure (P0) of hot water corresponding to the material temperature. The superheated water at high temperature and high pressure in the water-based emulsion is used as a medium for transmitting static pressure. The cross-linking curing time is controlled to be between 30 minutes and 3 hours. After the hot isostatic pressing treatment, the PCSP in the water-based emulsion is cross-linked and cured, and bubbles are prevented from being generated in the PCSP. Spray drying is continued or the material is slowly cooled and depressurized in a stepwise manner and then dried in a normal pressure oven to obtain cross-linked and cured spherical granular powder (Wholly Cross-linked Spherical Particles, hereinafter referred to as WCSP); the dried WCSP is further subjected to a carbonization treatment and a subsequent CVD surface sealing treatment in a loose or vibrated physical state; Step 5: Carbonization treatment The spherical particle powder WCSP which is not easy to stick after being fully cross-linked and cured is passed through a 200-mesh vibrating screen or subjected to air flow particle size sorting, and then subjected to a carbonization treatment in a loose or compacted natural stacking physical state; first, the material is heated to 190°C-230°C under the protection of air or an oxidizing atmosphere or an inert atmosphere, and a pulse high-pressure oxidation treatment is performed in this temperature range for 0-12 hours, and the container is filled with high-pressure oxygen or compressed air or compressed air mixed with ozone at a pressure between 0.40-1.6MPa. In each cycle, the high pressure is maintained. The peak time of the pulse is between 30min-2h, and then a part of the internal gas is discharged to reduce the pressure to 0.20-0.80MPa, and this cycle is repeated 0-N times; then the material is heated step by step to a maximum carbonization temperature between 700-1200°C under vacuum or inert atmosphere protection with positive pressure, and maintained for 1-6 hours. After the material is cooled, a spherical powder semi-finished product with a hard carbon-nano silicon island structure with nano-scale openings on the surface is obtained. At this time, the BET specific surface area of the spherical powder semi-finished product is greater than 18 square meters / gram, and a subsequent CVD surface sealing treatment is performed; Step 6: Use CVD to achieve surface sealing After the carbonization treatment in the above steps, a carbon source-containing gas such as methane, propane or ethylene is introduced into the material in a fluidized state, and conventional CVD chemical vapor deposition is used to achieve surface sealing; or pulse high-pressure chemical vapor deposition (PH-CVD) is used to achieve surface sealing when the material is in a loose or vibrated state: an inert gas with a pressure between 0.60 and 1.60 MPa is used as a carrier gas, and cyclohexane liquid or other hydrocarbons are used as a carbon source. The nanoscale micropores distributed on the surface of the spherical powder semi-finished product formed after the above-mentioned carbonization are used to adsorb the active gas polymer clusters formed after thermal evaporation or thermal cracking of the carbon source. After subsequent high-temperature thermal cracking, thermal polycondensation and other complex physical and chemical changes, an amorphous carbon coating layer is formed on the surface of the powder or inside the open micropores, thereby achieving surface sealing, reducing the BET specific surface area, and improving the battery's initial efficiency. The technical purpose; pulse high-pressure chemical vapor deposition (PH-C The specific technical operation of VD is as follows: when the material heating temperature is between 200℃-600℃, pulse high pressure chemical vapor deposition adopts the following multiple variable pressure cycle operations: use the internal gas pressure in the pressure range of 0.60-1.60MPa for high pressure pulse heat treatment for 1-2 hours, and then reduce the pressure to the low pressure range of 0.20-0.80MPa, and perform such pulse variable pressure for 6-20 cycles to achieve mass transfer and adsorption of active gas polymer clusters between powder gaps and on the surface of powder; after subsequent heating to the temperature range of 600℃-1300℃ for secondary carbonization treatment, pyrolytic carbon-type amorphous carbon is formed on the surface of the powder to achieve surface sealing and reduce the BET specific surface area of the spherical powder. After cooling to below 200℃ and taking out of the furnace, it is passed through a 200-mesh vibrating screen or air flow classification to remove magnetic foreign matter to obtain a hard carbon-graphite sea island structure spherical negative electrode material finished product, and its BET specific surface area is less than or equal to 6m 2 / g.
3. The method for manufacturing the hard carbon-nano silicon island structure spherical negative electrode material according to claim 1, characterized in that: The weight ratio of nano-silicon powder and precursor of hard carbon component in the raw materials is preferably controlled between 1:10 and 1:20 to obtain hard carbon-nano-silicon sea island structure spherical negative electrode material. The gram capacity of the product is between 500 and 750 mAh / g. The lithium-ion battery made from it has a 3C charge / 3C discharge cycle life of more than 1000 times.
Citation Information
Patent Citations
A novel pitch-based spherical porous doping method for modifying a hard carbon anode material
CN109037603A
Graphite-based negative electrode active material, preparation method and application thereof, and secondary battery
CN115312731A
High-energy-density fast-charging graphite negative electrode material and preparation method thereof, negative electrode plate and battery
CN117012936A